2003
DOI: 10.1128/jcm.41.3.1062-1068.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Broth Microdilution, E Test, and Agar Dilution Methods for Antibiotic Susceptibility Testing of Campylobacter jejuni and Campylobacter coli

Abstract: A standardized broth microdilution method was compared to the E test and an agar dilution method for the antimicrobial susceptibility testing of Campylobacter jejuni and C. coli isolates. A group of 47 human clinical isolates, 37 isolates from retail poultry, and 29 isolates from living turkeys (total, 113 isolates) was included in the study. These encompassed 92 C. jejuni and 21 C. coli strains. The MICs of six antimicrobial agents were determined by the broth microdilution and E test methods, and the strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 19 publications
6
95
0
3
Order By: Relevance
“…There are no parameters for the susceptibility profile of Campylobacter spp. (2,5), thus the interpretation of results an inhibition zone diameters followed the National Committee for Clinical Laboratory recommendations (8) for microorganisms requiring 5% CO2 for growth. The following bacteria were considered: Enterococcus for penicillin, amoxicillin and ampicillin, Streptococcus for tetracyclines and erythromycin, and Enterobacteriaceae for enrofloxacin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no parameters for the susceptibility profile of Campylobacter spp. (2,5), thus the interpretation of results an inhibition zone diameters followed the National Committee for Clinical Laboratory recommendations (8) for microorganisms requiring 5% CO2 for growth. The following bacteria were considered: Enterococcus for penicillin, amoxicillin and ampicillin, Streptococcus for tetracyclines and erythromycin, and Enterobacteriaceae for enrofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to measure the activity of the other antimicrobials and the TTC control disc, since there was no growth around the discs. The use of MH agar supplemented with 5% sheep blood (3,5) has been recommended in the literature. MH agar diffusion test compared to agar dilution test was considered to be reliable, easy-to-perform and inexpensive in monitoring the antimicrobial resistance of C. jejuni strains (2).…”
Section: Resultsmentioning
confidence: 99%
“…Several laboratory methods, including disc diffusion, broth microdilution, agar dilution and the Epsilometer-test (E-test) have been applied to determine in vitro susceptibility profile(s) of Campylobacter to a range of antimicrobial agents [15,41,45,46,48,84,119,149]. Despite the availability of comparable standardised procedures for many organisms, based on, the approved guidelines defined by the National Committee for Clinical Laboratory Standards (NCCLS), no internationally accepted criteria for susceptibility testing of Campylobacter spp.…”
Section: Antimicrobial Susceptibility Testing In Campylobacter Sppmentioning
confidence: 99%
“…Values determined however can vary depending on the antimicrobial agent(s) being considered [48]. This observation was particularly evident with respect to C. jejuni [84]. Comparing MIC values obtained by E-test and the agar dilution protocols, Ge et al [48] reported values ranging from 21.4 to 62% for gentamicin and nalidixic acid respectively.…”
Section: Antimicrobial Susceptibility Testing In Campylobacter Sppmentioning
confidence: 99%
See 1 more Smart Citation